Preparation method of lithium iron phosphate

By using carbon ball templates and air-fired technology in the preparation of lithium manganese iron phosphate materials, the problems of high raw materials and difficulty in industrial production in the existing technology are solved, and efficient and low-cost lithium manganese iron phosphate materials are achieved, which improves the conductive properties and compaction density of the material.

CN119683590APending Publication Date: 2025-03-25SHAANXI CHUANGPU NEW ENERGY TECH CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411798217.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing methods for preparing lithium manganese iron phosphate positive electrode materials for porous carbon templates have problems such as high raw material costs and difficulty in achieving industrial production.

Method used

Carbon spheres are used as templates to prepare ferromanganese oxide precursors and combine them with air-fired technology to improve the solid solution of ferromanganese and lithium manganese phosphate materials.

Benefits of technology

The preparation process is simplified, energy consumption is reduced, compaction density and electrochemical performance of lithium manganese iron phosphate material are improved, and the cost advantage is obvious.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683590A_ABST
    Figure CN119683590A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of lithium manganese iron phosphate. Comprising the following steps: S1, preparing ferromanganese oxide from an iron source and a manganese source; s2, performing impurity removal and drying on the ferromanganese oxide precursor to obtain the ferromanganese oxide precursor; s3, obtaining a lithium salt solution through a lithium source and a phosphorus source; s4, adding a glucose solution and the ferromanganese oxide precursor prepared in S2 into a lithium salt solution to obtain a mixed system; and S5, grinding the mixed system, performing spray drying, and performing high-temperature sintering to obtain the lithium manganese iron phosphate material. Compared with an existing sol-gel method, the method for preparing the lithium iron phosphate material through the solid phase method is simple in process, mild in preparation condition, low in calcination temperature and short in heat treatment time, and meanwhile the prepared porous lithium manganese iron phosphate material is high in compaction density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium iron phosphate preparation, and in particular to a method for preparing lithium iron phosphate. Background Art

[0002] Lithium-ion battery is an energy storage device that is widely used in the field of energy storage, power batteries and portable electronic devices. Lithium-ion batteries have advantages such as high operating voltage, low self-discharge and good safety. Lithium-ion batteries are mainly composed of positive electrode materials, negative electrode materials, electrolytes, diaphragms and shells. The positive electrode materials mainly include lithium cobalt oxide, cobalt, nickel binary system, nickel cobalt manganese ternary system, nickel cobalt aluminum ternary system, lithium iron phosphate, lithium manganese iron phosphate, etc. Among them, lithium iron phosphate (LFP) has the advantages of low cost, high safety and good cycle life. Lithium manganese iron phosphate (LMFP) is developed on the basis of lithium iron phosphate modification. It is a solid solution material composed of lithium iron phosphate and lithium phosphate. The crystal structure of lithium manganese iron phosphate is similar to that of lithium iron phosphate, and it has the characteristics of stable chemical properties and excellent safety performance. At the same time, the doped manganese element can increase the charging voltage of the material, increasing the charging voltage from 3.4V of lithium iron phosphate to 4.1V, which theoretically increases the battery energy density by 15-20%, further expanding the range of endurance. Therefore, the safety performance of LMFP is better than that of ternary materials, and the energy density is higher than that of LFP. In addition, LMFP has low dependence on rare metals and can be produced on the same line with LFP, with obvious cost advantages. However, the olivine crystal structure of LMFP itself makes its conductivity and rate performance poor. At the same time, the manganese element in the positive electrode changes and the Jahn-Teller effect occurs, and manganese ions are dissolved, resulting in increased battery polarization. The manganese element dissolved in the electrolyte will be deposited on the surface of the negative electrode, destroying the SEI layer structure, causing capacity loss and poor cyclability. The existing method for preparing lithium manganese iron phosphate positive electrode materials using porous carbon as a template is usually prepared by a sol-gel method. The raw materials used in this method must be pure substances, which not only has expensive raw materials and high costs, but also is difficult to achieve industrial production. Summary of the invention

[0003] The present invention provides a method for preparing lithium iron phosphate material, using carbon balls as templates to prepare ferromanganese precursors, providing a method for preparing lithium iron manganese phosphate with a simple preparation process, and improving the solid solution of ferromanganese through an empty firing process, thereby improving the overall conductivity and compaction density of the lithium iron manganese phosphate positive electrode material. The specific scheme is:

[0004] A method for preparing lithium manganese iron phosphate comprises the following steps:

[0005] S1. preparing manganese iron oxide using carbon balls, iron source and manganese source;

[0006] S2. removing impurities from the ferromanganese oxide precursor and drying it to obtain a ferromanganese oxide precursor;

[0007] S3. Obtaining a lithium salt solution through a lithium source and a phosphorus source;

[0008] S4. Adding glucose solution and manganese iron oxide precursor prepared in S2 to the lithium salt solution to obtain a mixed system;

[0009] S5. Grind the mixed system, spray dry it, and then sinter it at high temperature to obtain lithium manganese iron phosphate material.

[0010] Preferably, the preparation process of the ferromanganese oxide comprises:

[0011] First, carbon balls, iron salt, manganese salt and weak base are uniformly dispersed in deionized water to obtain a mixed solution A;

[0012] Then, the mixed solution A is heated to react, and after the reaction is complete, cooled to room temperature;

[0013] After that, remove the impurities;

[0014] Finally, the manganese iron oxide was obtained by vacuum drying.

[0015] Preferably, the average particle size of the carbon spheres is 200-500 nm.

[0016] Preferably, in the heating reaction, the reaction temperature is 150°C-200°C, and the reaction time is 2-12 hours.

[0017] Preferably, the reaction temperature is 180° C. and the reaction time is 10 h.

[0018] Preferably, in S2, the sintering temperature of the precursor of the manganese iron oxide is 300-400°C, the sintering time is 2-6h, and the heating rate is 1°C / min.

[0019] Preferably, in S3, the lithium source is selected from any one or more of lithium phosphate, lithium hydroxide, lithium carbonate, lithium sulfate, lithium oxalate, and alkyl lithium;

[0020] The phosphorus source is selected from any one or more of manganese dihydrogen phosphate, phosphoric acid, lithium phosphate, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and dilithium hydrogen phosphate.

[0021] Preferably, in the spray drying, the inlet temperature is 110-250°C, the outlet temperature is 70-150°C, the pressure is 0.3-0.8 MPa, and the flow rate is 10-80 rpm.

[0022] Preferably, in the high temperature sintering process, sintering is performed in a nitrogen or argon atmosphere;

[0023] The heating rate is 2-5℃ / min, the sintering temperature is 400-800℃, and the material is lithium manganese iron phosphate.

[0024] Compared with the prior art, the beneficial effects of this application are:

[0025] The present application provides a method for preparing a lithium iron phosphate material by a solid phase method. Compared with the existing sol-gel method, the present application has a simple preparation process, mild preparation conditions, low calcination temperature, short heat treatment time, and more energy saving. At the same time, the compaction density of the porous lithium manganese iron phosphate material prepared by the method described in the present application is relatively high, which can reach 2.2-2.4 g / cm 3 ;

[0026] At the same time, in the method for preparing the ferromanganese oxide precursor of the present application, a method of introducing carbon balls as a template to prepare the ferromanganese oxide is adopted to improve the crystallinity of the ferromanganese oxide, thereby helping the ferromanganese precursor to have a better morphology, and avoiding manganese precipitation by improving the crystallinity of the ferromanganese precursor, and then combining the sintering with oxygen for a second carbon coating to further simulate manganese precipitation;

[0027] Furthermore, in the present application, carbon spheres with an average particle size of 200-500 nm are used as templates to achieve easy removal by oxidation into gas at a temperature lower than the phase formation temperature of lithium manganese iron phosphate, leaving pores or channels, which are beneficial to lithium ion transmission. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a scanning electron microscope image of the lithium manganese iron phosphate sample prepared in Example 3 of the present application. DETAILED DESCRIPTION

[0029] A method for preparing lithium manganese iron phosphate comprises the following steps:

[0030] Step 1, uniformly dispersing a carbon ball solution, an iron salt, a manganese salt and a weak base in deionized water to obtain a mixed solution A;

[0031] Step 2, adding the mixed solution A to a heated reaction kettle, reacting at 150° C.-200° C. for 2-12 hours, and then cooling to room temperature, removing impurities in the product, and vacuum drying the obtained product to avoid oxidation and the influence of impurities on the product, thereby obtaining a precursor of manganese iron oxide;

[0032] Step 3: sinter the precursor of manganese iron oxide at 380° C. for 4 hours at a heating rate of 1° C. / min to obtain manganese iron oxide material.

[0033] Step 4, dissolving a lithium source and a phosphorus source in deionized water to obtain a mixed solution B, wherein the lithium source is selected from one or more of lithium phosphate, lithium hydroxide, lithium carbonate, lithium sulfate, lithium oxalate, alkyl lithium, etc., and the phosphorus source is selected from one of manganese dihydrogen phosphate, phosphoric acid, lithium phosphate, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, dilithium hydrogen phosphate, etc., to form a uniform solution, and adding the manganese iron oxide material prepared in the above step 3 to the lithium salt solution to obtain a mixed system;

[0034] Step 5, grinding the mixed slurry of the mixed system, grinding to a certain particle size and then spray drying; spray drying: inlet temperature 110-250°C, outlet temperature 70-150°C, pressure 0.3-0.8Mpa, flow rate 10-80rpm; then high-temperature sintering the spray-dried material: sintering in nitrogen or argon atmosphere, heating rate of 2-5°C / min, sintering temperature of 400-800°C, and finally obtaining lithium manganese iron phosphate material.

[0035] Wherein, in step 1, a mixed solution A is obtained by adding a carbon ball solution with a concentration of 2.5 g / L and standing for 48 hours to allow the carbon balls to fully adsorb ferrous ions and manganous ions;

[0036] The preparation method of the carbon sphere solution is as follows: dissolving carbon spheres with an average particle size of 200-500 nm in deionized water to prepare a carbon sphere solution with a concentration of 2.5 g / L.

[0037] The reaction temperature in step 2 is preferably 180° C., and the reaction time is preferably 10 h.

[0038] The sintering temperature in step 5 is preferably 700° C. The heating rate in step 5 is preferably 5° C. / min.

[0039] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Example 1

[0041] Step 1, add Fe(NO3)2·6H2O and Mn(NO3)2·4H2O in a molar ratio of 4:6 into 8L of water, stir and disperse them uniformly, add citric acid, and let stand for 24 hours to obtain a uniformly dispersed suspension;

[0042] Step 2, transfer 8L of the suspension into a 10L reactor, react at 180°C for 10h to obtain a product, cool the product naturally to room temperature, wash it with deionized water and ethanol three times respectively, and then filter it to remove impurities in the product, and vacuum dry it at 60°C for 24h to obtain manganese iron oxide powder;

[0043] Step 3, using 1000 ml of deionized water as a solvent, first add 70 g of glucose and 30 g of PEG2000 and stir to form a solution, then add 1000 g of the manganese iron oxide powder prepared in step 2 and stir for 30 minutes to obtain a manganese iron oxide solution;

[0044] Step 4, dissolving lithium carbonate and phosphoric acid in deionized water to form a uniform lithium salt solution, and adding the manganese iron oxide material prepared in the above step 3 to the lithium salt solution to obtain a manganese iron oxide mixed system;

[0045] Step 5, grinding, spray drying and high-temperature sintering the manganese iron oxide mixed system in sequence to obtain a pre-sintered material, wherein:

[0046] The grinding process is as follows: the slurry is ground to 1.1 microns in a coarse grinder, and then introduced into a fine grinder to be ground to 350-400 nanometers;

[0047] The spray drying process was as follows: inlet temperature 220°C, outlet temperature 110°C, flow rate 40rpm, and pressure 0.45Mpa.

[0048] The high temperature sintering process is as follows: pre-sintering material is obtained after keeping the temperature at 700°C for 8 hours in a tube.

[0049] Example 2

[0050] Step 1, prepare 8L of 2.5g / L carbon ball solution, first ultrasonicate in an ultrasonic cell crusher for 15 minutes, then fully stir and disperse under ultrasound until uniform, add Fe(NO3)2·6H2O and Mn(NO3)2·4H2O with a molar ratio of 4:6 to the carbon ball solution, stir and disperse evenly, add citric acid, and let stand for 24 hours to obtain a uniformly dispersed suspension (i.e., mixed solution A);

[0051] Step 2, transfer 8L of the suspension into a 10L reactor, react at 180°C for 10h to obtain a product, cool the product naturally to room temperature, wash it with deionized water and ethanol three times, and then filter it to remove impurities in the product, and vacuum dry it at 60°C for 24h to obtain a carbon ball @ manganese iron precursor;

[0052] The obtained carbon ball@ferromanganese precursor was placed in a porcelain boat, heated to 300°C at a heating rate of 1°C / min in an air atmosphere and kept at this temperature for 2 hours to obtain ferromanganese oxide powder;

[0053] Step 3, using 1000 ml of deionized water as solvent, first adding 100 g of glucose and stirring to form a solution, then adding 1000 g of the manganese iron oxide sample prepared in step 2, and stirring for 30 min to obtain a manganese iron oxide solution;

[0054] Step 4, dissolving lithium carbonate and phosphoric acid in deionized water to form a uniform lithium salt solution (i.e., mixed solution B), and adding the manganese iron oxide material prepared in the above step 3 to the lithium salt solution to obtain a manganese iron oxide mixed system;

[0055] Step 5, grinding, spray drying and high-temperature sintering the manganese iron oxide mixed system in sequence to obtain a pre-sintered material, wherein:

[0056] The sand grinding process is as follows: the slurry is ground to 1.1 microns in a coarse grinder, and then introduced into a fine grinder to grind to 350-400 nanometers;

[0057] The spray drying process was: inlet temperature 220°C, outlet temperature 110°C, flow rate 40rpm, pressure 0.45Mpa;

[0058] The high temperature sintering process is as follows: pre-sintering material is obtained after keeping the temperature at 700°C for 8 hours in a tube.

[0059] Example 3

[0060] Step 1, prepare 8L of 2.5g / L carbon ball solution, first ultrasonicate in an ultrasonic cell crusher for 15 minutes, then fully stir and disperse under ultrasound until uniform, add Fe(NO3)2·6H2O and Mn(NO3)2·4H2O with a molar ratio of 4:6 to the carbon ball solution, stir and disperse evenly, add citric acid, and let stand for 24 hours to obtain a uniformly dispersed suspension (i.e., mixed solution A);

[0061] Step 2, transfer 8L of the suspension into a 10L reactor, react at 180°C for 10h to obtain a product, cool the product naturally to room temperature, wash it with deionized water and ethanol three times, and then filter it to remove impurities in the product, and vacuum dry it at 60°C for 24h to obtain a carbon ball @ manganese iron precursor;

[0062] The obtained carbon ball@ferromanganese precursor was placed in a porcelain boat, heated to 380°C at a heating rate of 1°C / min in an air atmosphere and kept at this temperature for 4 hours to obtain ferromanganese oxide powder;

[0063] Step 3, using 1000 ml of deionized water as solvent, first add 70 g of glucose and 30 g of PEG2000 and stir to form a solution, then add 1000 g of the manganese iron oxide sample prepared in step 2, and stir for 30 min to obtain a manganese iron oxide solution;

[0064] Step 4, dissolving lithium carbonate and phosphoric acid in deionized water to form a uniform lithium salt solution (i.e., mixed solution B), and adding the manganese iron oxide material prepared in the above step 3 to the lithium salt solution to obtain a manganese iron oxide mixed system;

[0065] Step 5, grinding, spray drying and high-temperature sintering the manganese iron oxide mixed system in sequence to obtain a pre-sintered material, wherein:

[0066] The sand grinding process is as follows: the slurry is ground to 1.1 microns in a coarse grinder, and then introduced into a fine grinder to grind to 350-400 nanometers;

[0067] The spray drying process was: inlet temperature 220°C, outlet temperature 110°C, flow rate 40rpm, pressure 0.45Mpa;

[0068] The high temperature sintering process is as follows: putting it into a tube and keeping it at 700°C for 8 hours to obtain the pre-burned material.

[0069] Example 4

[0070] Step 1, prepare 8L of 2.5g / L carbon ball solution, first ultrasonicate in an ultrasonic cell crusher for 15 minutes, then fully stir and disperse under ultrasound until uniform, add Fe(NO3)2·6H2O and Mn(NO3)2·4H2O with a molar ratio of 4:6 to the carbon ball solution, stir and disperse evenly, add citric acid, let stand for 24 hours, and obtain a uniformly dispersed suspension (i.e., mixed solution A);

[0071] Step 2, transfer 8L of the suspension into a 10L reactor, react at 180°C for 10h to obtain a product, cool the product naturally to room temperature, wash it with deionized water and ethanol three times, filter it to remove impurities in the product, and vacuum dry it at 60°C for 24h to obtain a carbon ball @ manganese iron precursor;

[0072] The obtained carbon ball@ferromanganese precursor was placed in a porcelain boat, heated to 380°C at a heating rate of 1°C / min in an air atmosphere and kept warm for 4 hours to obtain ferromanganese oxide powder.

[0073] Step 3, using 1000 ml of deionized water as solvent, first add 50 g of glucose and 50 g of PEG2000 and stir to form a solution, then add 1000 g of the manganese iron oxide sample prepared in step 2, and stir for 30 min to obtain a manganese iron oxide solution;

[0074] Step 4, dissolving lithium carbonate and phosphoric acid in deionized water to form a uniform lithium salt solution (i.e., mixed solution B), and adding the manganese iron oxide material prepared in the above step 3 to the lithium salt solution to obtain a manganese iron oxide mixed system;

[0075] Step 5, grinding, spray drying and high-temperature sintering the manganese iron oxide mixed system in sequence to obtain a pre-sintered material, wherein:

[0076] The sand grinding process is as follows: the slurry is ground to 1.1 microns in a coarse grinder, and then introduced into a fine grinder to grind to 350-400 nanometers;

[0077] The spray drying process was: inlet temperature 220°C, outlet temperature 110°C, flow rate 40rpm, pressure 0.45Mpa;

[0078] The high temperature sintering process is as follows: putting it into a tube and keeping it at 700°C for 8 hours to obtain the pre-burned material.

[0079] Example 5

[0080] Step 1, prepare 8L of 2.5g / L carbon ball solution, first ultrasonicate in an ultrasonic cell crusher for 15 minutes, then fully stir and disperse under ultrasound until uniform, add Fe(NO3)2·6H2O and Mn(NO3)2·4H2O to the carbon ball solution at a molar ratio of 4:6, stir and disperse evenly, add citric acid, and let stand for 24 hours to obtain a uniformly dispersed suspension (i.e., mixed solution A);

[0081] Step 2, transfer 8L of the suspension into a 10L reactor, react at 180°C for 10h to obtain a product, cool the product naturally to room temperature, wash it with deionized water and ethanol three times, and then filter it to remove impurities in the product, and vacuum dry it at 60°C for 24h to obtain a carbon ball @ manganese iron precursor;

[0082] The carbon ball @ ferromanganese precursor was placed in a porcelain boat, heated to 380°C at a heating rate of 1°C / min in an air atmosphere and kept at this temperature for 4 hours to obtain ferromanganese oxide powder;

[0083] Step 3, using 1000 ml of deionized water as solvent, first add 100 g of PEG2000 and stir to form a solution, then add 1000 g of the manganese iron oxide sample prepared in step 2, and stir for 30 min to obtain a manganese iron oxide solution;

[0084] Step 4, dissolving lithium carbonate and phosphoric acid in deionized water to form a uniform lithium salt solution (i.e., mixed solution B), and adding the manganese iron oxide material prepared in the above step 3 to the lithium salt solution to obtain a manganese iron oxide mixed system;

[0085] Step 5, grinding, spray drying and high-temperature sintering the manganese iron oxide mixed system in sequence to obtain a pre-sintered material, wherein:

[0086] The sand grinding process is as follows: the slurry is ground to 1.1 microns in a coarse grinder, and then introduced into a fine grinder to grind to 350-400 nanometers;

[0087] The spray drying sand milling process was: inlet temperature 220°C, outlet temperature 110°C, flow rate 40rpm, pressure 0.45Mpa;

[0088] The high temperature sintering sand grinding process is as follows: sending it into a tube and keeping it at 700°C for 8 hours to obtain the pre-burned material.

[0089] Example 6

[0090] Step 1: Prepare 8 L of 2.5 g / L carbon ball solution, ultrasonicate it in an ultrasonic cell crusher for 15 minutes, and then stir and disperse it evenly under ultrasound. 3)2 4H2O was added to the carbon sphere solution at a molar ratio of 4:6, and after being stirred and dispersed evenly, citric acid was added and allowed to stand for 24 hours to obtain a uniformly dispersed suspension (i.e., mixed solution A);

[0091] Step 2, transfer 8L of the suspension into a 10L reactor, react at 180°C for 10h to obtain a product, cool the product naturally to room temperature, wash it with deionized water and ethanol three times, and then filter it to remove impurities in the product, and vacuum dry it at 60°C for 24h to obtain a carbon ball @ manganese iron precursor;

[0092] The obtained carbon ball @ ferromanganese precursor was placed in a porcelain boat, heated to 380°C at a heating rate of 1°C / min in an air atmosphere and kept warm for 4 hours to obtain ferromanganese oxide powder.

[0093] Step 3, using 1000 ml of deionized water as solvent, first add 70 g of glucose and 30 g of PEG2000 and stir to form a solution, then add 1000 g of the manganese iron oxide sample prepared in step 2, and stir for 30 min to obtain a manganese iron oxide solution;

[0094] Step 4, dissolving lithium carbonate and phosphoric acid in deionized water to form a uniform lithium salt solution (i.e., mixed solution B), and adding the manganese iron oxide material prepared in the above step 3 to the lithium salt solution to obtain a manganese iron oxide mixed system;

[0095] Step 5, grinding, spray drying and high-temperature sintering the manganese iron oxide mixed system in sequence to obtain a pre-sintered material, wherein:

[0096] The sand grinding process is as follows: the slurry is ground to 1.1 microns in a coarse grinder, and then introduced into a fine grinder to grind to 350-400 nanometers;

[0097] The spray drying process was: inlet temperature 220°C, outlet temperature 110°C, flow rate 40rpm, pressure 0.45Mpa;

[0098] The high temperature sintering process is as follows: putting it into a tube and keeping it at 650°C for 8 hours to obtain the pre-burned material.

[0099] Example 7

[0100] Step 1, prepare 8L of 2.5g / L carbon ball solution, first ultrasonicate in an ultrasonic cell crusher for 15 minutes, then fully stir and disperse under ultrasound until uniform, add Fe(NO3)2·6H2O and Mn(NO3)2·4H2O to the carbon ball solution at a molar ratio of 4:6, stir and disperse evenly, add citric acid, let stand for 24 hours, and obtain a uniformly dispersed suspension (i.e., mixed solution A);

[0101] Step 2, transfer 8L of the suspension into a 10L reactor, react at 180°C for 10h to obtain a product, cool the product naturally to room temperature, wash it with deionized water and ethanol three times, and then filter it to remove impurities in the product, and vacuum dry it at 60°C for 24h to obtain a carbon ball @ manganese iron precursor;

[0102] The obtained carbon ball@ferromanganese precursor was placed in a porcelain boat, heated to 380°C at a heating rate of 1°C / min in an air atmosphere and kept warm for 4 hours to obtain ferromanganese oxide powder.

[0103] Step 3, using 1000 ml of deionized water as solvent, first add 70 g of glucose and 30 g of PEG2000 and stir to form a solution, then add 1000 g of the manganese iron oxide sample prepared in step 2, and stir for 30 min to obtain a manganese iron oxide solution;

[0104] Step 4, dissolving lithium carbonate and phosphoric acid in deionized water to form a uniform lithium salt solution (i.e., mixed solution B), and adding the manganese iron oxide material prepared in the above step 3 to the lithium salt solution to obtain a manganese iron oxide mixed system;

[0105] Step 5, grinding, spray drying and high-temperature sintering the manganese iron oxide mixed system in sequence to obtain a pre-sintered material, wherein:

[0106] The sand grinding process is as follows: the slurry is ground to 1.1 microns in a coarse grinder, and then introduced into a fine grinder to grind to 350-400 nanometers;

[0107] The spray drying process was: inlet temperature 220°C, outlet temperature 110°C, flow rate 40rpm, pressure 0.45Mpa;

[0108] The high temperature sintering process is as follows: putting it into a tube and keeping it at 750°C for 8 hours to obtain the pre-burned material.

[0109] Example 8

[0110] Step 1, prepare 8L of 2.5g / L carbon ball solution, first ultrasonicate in an ultrasonic cell crusher for 15 minutes, then fully stir and disperse under ultrasound until uniform, add Fe(NO3)2·6H2O and Mn(NO3)2·4H2O to the carbon ball solution at a molar ratio of 4:6, stir and disperse evenly, add citric acid, let stand for 24 hours, and obtain a uniformly dispersed suspension (i.e., mixed solution A);

[0111] Step 2, transfer 8L of the suspension into a 10L reactor, react at 180°C for 10h to obtain a product, cool the product naturally to room temperature, wash it with deionized water and ethanol three times, filter it to remove impurities in the product, and vacuum dry it at 60°C for 24h to obtain a carbon ball @ manganese iron precursor;

[0112] The obtained carbon ball@ferromanganese precursor was placed in a porcelain boat, heated to 400°C at a heating rate of 1°C / min in an air atmosphere and kept warm for 6 hours to obtain ferromanganese oxide powder.

[0113] Step 3, using 1000 ml of deionized water as solvent, first add 70 g of glucose and 30 g of PEG2000 and stir to form a solution, then add 1000 g of the manganese iron oxide sample prepared in step 2, and stir for 30 min to obtain a manganese iron oxide solution;

[0114] Step 4, dissolving lithium carbonate and phosphoric acid in deionized water to form a uniform lithium salt solution (i.e., mixed solution B), and adding the manganese iron oxide material prepared in the above step 3 to the lithium salt solution to obtain a manganese iron oxide mixed system;

[0115] Step 5, grinding, spray drying and high-temperature sintering the manganese iron oxide mixed system in sequence to obtain a pre-sintered material, wherein:

[0116] The sand grinding process is as follows: the slurry is ground to 1.1 microns in a coarse grinder, and then introduced into a fine grinder to grind to 350-400 nanometers;

[0117] The spray drying process was: inlet temperature 220°C, outlet temperature 110°C, flow rate 40rpm, pressure 0.45Mpa;

[0118] The high temperature sintering process is as follows: putting it into a tube and keeping it at 850°C for 8 hours to obtain the pre-burned material.

[0119] Comparative Example

[0120] (1) Mixing:

[0121] 1660 kg of phosphoric acid was added to 1000 L of deionized water, followed by stirring for 2 minutes, and then 920 kg of lithium carbonate was added, followed by stirring for 20 minutes, and then Fe(NO3)2·6H2O and Mn(NO3)2·4H2O were added at a molar ratio of 4:6 and stirred for 7 minutes. Then, 70 g of glucose and 30 g of PEG2000 were added, stirred for 7 minutes, and then fed into a coarse grinder.

[0122] (2) Sanding:

[0123] The slurry was ground to 1.3 microns in a coarse grinder and then introduced into a fine grinder and ground to 300-400 nanometers.

[0124] (3) Spray drying:

[0125] Inlet temperature 220℃, outlet temperature 110℃, flow rate 40rpm, pressure 0.45Mpa.

[0126] (4) High temperature sintering:

[0127] The pre-burned material was sent into a kiln and kept at 700°C for 8 hours.

[0128] Performance Evaluation

[0129] The lithium manganese iron phosphate obtained in the above embodiments 1 to 8 and the comparative example was dispersed in NMP solvent according to the active material: superP: PVDF = 95:2.5:2.5 to prepare a slurry, and the slurry was coated on an aluminum foil to prepare a pole piece, and a button battery was prepared with the pole piece as the positive electrode and the lithium sheet as the negative electrode. The lithium manganese iron phosphate obtained in the above embodiments 1 to 8 and the comparative example was tested for compaction density and energy storage performance. The test results are shown in Table 1.

[0130] Table 1 Battery rate performance

[0131] sample <![CDATA[0.2C discharge capacity / mAh g -1 > <![CDATA[1C discharge capacity / mAh g -1 > <![CDATA[Compaction density / cm 3 g -1 > Example 1 150 142 2.10 Example 2 150 140 2.20 Example 3 155 145 2.35 Example 4 151 132 2.30 Example 5 149 130 2.45 Example 6 153 125 2.25 Example 7 145 123 2.37 Example 8 143 120 2.42 Comparative Example 148 128 2.08

[0132] It can be seen from the results in Table 1 that the discharge capacity of the lithium manganese iron phosphate prepared in this application at 0.2C is 143-155 mAhg -1 ; The highest can reach 155mAhg -1 , prepared by the method of real-time example 3; the discharge capacity at 1C is 120-145Ahg -1 , up to 145Ahg -1 , which is prepared in Example 3, while the discharge capacity of the comparative example at 0.2C is 145 mAhg -1 , the discharge capacity at 1C is 128Ahg -1 It can be concluded that the lithium manganese iron phosphate prepared in this application has good electrochemical performance;

[0133] Compacted density is 2.10-2.45cm 3 g -1 , up to 2.45cm 3 g -1 , while the comparative example is 2.08, from which it can be concluded that the lithium manganese iron phosphate prepared in the present application is a high-density lithium manganese iron phosphate;

[0134] The difference between the comparative example and embodiment 3 is:

[0135] 1. The comparative example adopts the sol-gel method, while Example 3 of the present application adopts the solid phase method. Compared with the comparative example, the preparation process of Example 3 is simpler;

[0136] 2. Example 3: Introducing carbon sphere template to synthesize manganese iron oxide,

[0137] 3. Then add oxygen for sintering to remove the carbon ball template, so that the ferromanganese precursor has a better morphology and improves the crystallinity of ferromanganese oxide; then combine with oxygen sintering,

[0138] 4. Improve the crystallinity, make the crystallinity of lithium iron phosphate material more uniform, and simulate the precipitation of manganese;

[0139] 5. Using deionized water as solvent, glucose and PEG2000 were added and stirred to form a solution, and the manganese iron oxide was subjected to secondary carbon coating to further simulate the precipitation of manganese.

[0140] Figure 1 This is a scanning electron microscope image of the lithium manganese iron phosphate sample prepared in Example 3. Figure 1 It can be seen that the lithium manganese iron phosphate particles synthesized by this method are uniform, mainly porous spherical, and the primary particle size is 10-800nm. It can be concluded that compared with the lithium manganese iron phosphate obtained by the conventional solid phase preparation method, which is mainly long and narrow, the product synthesized in this application is mainly spherical, and has the advantages of high compaction and high ion conductivity.

[0141] In summary, the solid phase manufacturing process of the lithium manganese iron phosphate prepared in the present application is simple and easy to implement, and the prepared lithium manganese iron phosphate has good electrochemical properties, and the prepared lithium manganese iron phosphate is a high-density lithium manganese iron phosphate.

[0142] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for preparing lithium manganese iron phosphate, characterized in that: The following steps are involved: S1. preparing manganese iron oxide using carbon balls, iron source and manganese source; S2. removing impurities from the ferromanganese oxide precursor and drying it to obtain a ferromanganese oxide precursor; S3. Obtaining a lithium salt solution through a lithium source and a phosphorus source; S4. Adding glucose solution and manganese iron oxide precursor prepared in S2 to the lithium salt solution to obtain a mixed system; S5. Grind the mixed system, spray dry it, and then sinter it at high temperature to obtain lithium manganese iron phosphate material.

2. The method for preparing lithium manganese iron phosphate according to claim 1, characterized in that: The preparation process of the ferromanganese oxide comprises: First, carbon balls, iron salt, manganese salt and weak base are uniformly dispersed in deionized water to obtain a mixed solution A; Then, the mixed solution A is heated to react, and after the reaction is complete, cooled to room temperature; After that, remove the impurities; Finally, the manganese iron oxide was obtained by vacuum drying.

3. A method for preparing lithium manganese iron phosphate according to claim 2, characterized in that: The average particle size of the carbon spheres is 200-500 nm.

4. A method for preparing lithium manganese iron phosphate according to claim 2, characterized in that: In the heating reaction, the reaction temperature is 150°C-200°C, and the reaction time is 2-12 hours.

5. A method for preparing lithium manganese iron phosphate according to claim 4, characterized in that: The reaction temperature is preferably 180° C., and the reaction time is preferably 10 h.

6. The method for preparing lithium manganese iron phosphate according to claim 1, characterized in that: In S2, the sintering temperature of the precursor of manganese iron oxide is 300-400°C, the sintering time is 2-6h, and the heating rate is 1°C / min.

7. The method for preparing lithium manganese iron phosphate according to claim 1, characterized in that: In S3, the lithium source is selected from any one or more of lithium phosphate, lithium hydroxide, lithium carbonate, lithium sulfate, lithium oxalate, and alkyl lithium; The phosphorus source is selected from any one or more of manganese dihydrogen phosphate, phosphoric acid, lithium phosphate, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and dilithium hydrogen phosphate.

8. The method for preparing lithium manganese iron phosphate according to claim 1, characterized in that: In spray drying, the inlet temperature is 110-250°C, the outlet temperature is 70-150°C, the pressure is 0.3-0.8Mpa, and the flow rate is 10-80rpm.

9. The method for preparing lithium manganese iron phosphate according to claim 1, characterized in that: In the high temperature sintering process, sintering is performed in a nitrogen or argon atmosphere; The heating rate is 2-5℃ / min, the sintering temperature is 400-800℃, and the material is lithium manganese iron phosphate.

Citation Information

Cited By

  • High-temperature-resistant low-iron-dissolution lithium iron phosphate material as well as preparation method and application thereof

    CN120664513A

  • Method for preparing high-compaction lithium manganese iron phosphate positive electrode material

    CN121573663A